2015
DOI: 10.1038/nchembio.1964
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of smORF-encoded bioactive polypeptides

Abstract: Analysis of genomes, transcriptomes, and proteomes reveals the existence of hundreds to thousands of translated, yet non-annotated short open reading frames (small ORFs or smORFs). The discovery of smORFs, and their protein products, smORF-encoded polypeptides (SEPs), reveals a fundamental gap in our knowledge of protein-coding genes. Different studies have identified central roles for smORFs in metabolism, apoptosis, and development. The discovery of these bioactive SEPs emphasizes the functional potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
250
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(251 citation statements)
references
References 83 publications
1
250
0
Order By: Relevance
“…[3][4][5] Moreover, peptide products can be detected with increased sensitivity by improved mass-spectrometry. [6][7][8][9][10][11][12] Based on these studies it is becoming increasingly clear that many regions outside of annotated protein-coding ORFs are translated. New translated regions have not only been identified in transcripts thought to be non-coding, but also upstream of a large fraction of protein-coding ORFs (so-called upstream ORFs, uORFs).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Moreover, peptide products can be detected with increased sensitivity by improved mass-spectrometry. [6][7][8][9][10][11][12] Based on these studies it is becoming increasingly clear that many regions outside of annotated protein-coding ORFs are translated. New translated regions have not only been identified in transcripts thought to be non-coding, but also upstream of a large fraction of protein-coding ORFs (so-called upstream ORFs, uORFs).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of evidence that lncRNA can produce short peptides from small open reading frames (smORFs) to regulate biological processes (51). The status of both lncRNA, and indeed, smORFs remains to be investigated in SCST.…”
Section: The 'Mirna-ome' and Other Non-coding Rnasmentioning
confidence: 99%
“…A number of GBPs are small proteins, less than 150 amino acids, and over the past decades the functions of many small proteins have been discovered to be critical to various cellular processes, primarily through serendipitous studies (16). For example, galectin-1 with an affinity for β-galactose (Gal) was shown to be essential to neuronal cell differentiation and be associated with malignant tumor progression in human (17,18).…”
mentioning
confidence: 99%
“…For example, galectin-1 with an affinity for β-galactose (Gal) was shown to be essential to neuronal cell differentiation and be associated with malignant tumor progression in human (17,18). Small proteins also regulate essential cellular processes of bacteria (e.g., the 43-aa SgrS) (19), yeast (20), and animals (16). In recent years, systems biology studies have demonstrated that organisms commonly express hundreds of small proteins that often have no characterized homologs (16,(21)(22)(23).…”
mentioning
confidence: 99%
See 1 more Smart Citation